2022
DOI: 10.3390/cancers14071828
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric Magnetic Resonance Imaging Grades the Aggressiveness of Prostate Cancer

Abstract: We sought to find further evidence showing the increase in PCa aggressiveness as PI-RADS score increases from four surrogates of PCa aggressiveness: i. prostate biopsy GG (≤3 vs. >3), ii. type of pathology in surgical specimens (favourable vs. unfavourable), iii. clinical stage (localised vs. advanced), and risk of recurrence of localised PCa after primary treatment (low-intermediate vs. high). A group of 692 PCa patients were diagnosed after 3-T multiparametric MRI (mpMRI) and guided and/or systematic biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Numerous studies in the literature investigated the relationship between PI-RADS categories and various prognostic factors. Morote et al 32 demonstrated the association between the PI-RADS group and PCa aggressiveness. Similar to our study, Morote et al’s 32 work also found that the PI-RADS ≥4 patient group was significantly more associated with aggressive cancers compared to the PI-RADS ≤3 group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in the literature investigated the relationship between PI-RADS categories and various prognostic factors. Morote et al 32 demonstrated the association between the PI-RADS group and PCa aggressiveness. Similar to our study, Morote et al’s 32 work also found that the PI-RADS ≥4 patient group was significantly more associated with aggressive cancers compared to the PI-RADS ≤3 group.…”
Section: Discussionmentioning
confidence: 99%
“…Morote et al 32 demonstrated the association between the PI-RADS group and PCa aggressiveness. Similar to our study, Morote et al’s 32 work also found that the PI-RADS ≥4 patient group was significantly more associated with aggressive cancers compared to the PI-RADS ≤3 group. Alessi et al 33 reported that a low PI-RADS score (PI-RADS ≤3) independently excluded the presence of extraprostatic extension with a sensitivity of 99% and a negative predictive value of 98%, irrespective of clinical risk group.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the multivariable analysis, the cut-off value did not impact the cancer detection significantly. This may be due to the overall ambivalent detection rate of PI-RADS 3 that has been well documented in the literature [ 35 , 36 ]. The detection rate of csPCa for PI-RADS 3 was only 21/432 (10.4%) in our cohort and, therefore, the influence of factors, such as age or volume, might be underpowered in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that could MRI only find morphological information and was not able to obtain the internal microstructure of tumor tissues, resulting in difficult evaluation for the risk of prostate tumors [ 6 ]. Another study showed that diffusion-weighted MRI could well manifest the tissue of tumor with abundant vascularity; however, the diagnostic role for prostate malignant tumor was debated [ 7 ]. In conclusion, MRI has the advantages of thorough research and clear morphological information and can better display tumor tissues with abundant blood vessels.…”
Section: Introductionmentioning
confidence: 99%